Effects of relay cover crop planting date on their biomass and maize productivity in a sub-humid region of Zimbabwe under conservation agriculture. (1st September 2016) - Mhlanga, Blessing; Cheesman, Stephanie; Maasdorp, Barbara; Mupangwa, Walter; Munyoro, Colleta; Sithole, Cephas; Thierfelder, Christian
Highlights: Success of relay intercropping depends on distribution of dry spells of the season. Biomass productivity from relay cover crops depends on the type of cover crop. Late planting of relay cover crops compromises their growth and development. Late planting of cover crops results in insignificant total plot biomass increases. Herbicides may be used to control relay crop regrowth late in the dry season. Abstract: Relay cropping of cover crops is a strategy of increasing biomass yields and productivity of maize-based systems. However, there is need to strategically plan the relay cropping to avoid competition between the main crop and the relay cover crops while at the same time obtaining optimum yields from both crops. A study was carried out in a clay soil in a sub-humid region of Zimbabwe to investigate the effect of introducing different relay cover crops at 8, 11 and 15 weeks after planting maize (WAPM) into a standing maize crop on biomass yield of the relay cover crops, their emergence and maize yields in the 2012–13 and 2013–14 seasons. From the results of the study, it was observed that the introduction of relay cover crops late in the season compromises their emergence and hence biomass yields (as low as 0.8 kg ha −1 for blue lupins ( Lupinus angustifolius var. angustifolius (L.)). In a season where longer mid-season dry spells were experienced (2013–14), biomass yields of the relay cover crops were lower than in 2012–13 season. Delays in planting of relay cover crops (i.e. from 8 to 11 and from 11 to 15 WAPM) resulted in yield reductions of around 50%. Relay cover crops introduced at different periods of the season had no significant effects on maize grain and biomass yields. However, there are relay cover crops such as the velvet bean ( Mucuna pruriens (L.) DC) and common oats ( Avena sativa L.) that showed better emergence even in the sub-optimal conditions (with emergence as high as 90%). Of all the investigated relay cover crops, none could contribute to significant amounts of biomass thus insignificant increases in total plot biomass. There is need to investigate on other earlier planting dates that do not compromise the biomass productivity of such relay cover crops.